(untitled) (Tribhuvan University Journal of Microbiology, 2020)
Objectives: To determine prevalence of Methicillin Resistant Staphylococcus aureus in different clinical specimens and biofilm production along with antimicrobial susceptibility pattern of isolates. Methods: Cross-sectional study was conducted from September 2019 to February 2020at Sukraraj Tropical and Infectious Disease Hospital. Total 3091 clinical specimens like blood, urine, sputum, pus, swab, body fluid were processed. Identification was done on the basis of colony characteristics, gram staining, culture in Mannitol Salt Agar, coagulase and oxidation fermentation test. Antibiotic susceptibility test and biofilm detection were performed by Kirby Bauer’s disc diffusion methods and Tissue Culture Plate technique (TCP) respectively. Methicillin resistant Staphylococcus species were detected by using Cefoxitin disc. Results: Out of 52 Staphylococcus species, 39 were Staphylococcus aureus and 13 were Coagulase negative Staphylococcus species. Highest numbers of Staphylococcus species were isolated from blood Sixteen (30.8%) were Methicillin resistant Staphylococcus aureus (MRSA) and 5(9.6%) were Methicillin resistant Coagulase negative Staphylococcus species. There was no significant association (p=0.25) between age group and prevalence of MRSA, MSSA, MRCoNS and MSCoNS. Methicillin resistant Staphylococcus species were resistant to antibiotics like amoxicillin, cloxacillin, erythromycin and higher sensitivity was found in gentamycin. Among 52 Staphylococcal isolates, 11(21.1%) were biofilm producers and 41(78.9%) were non biofilm producers. 90.9%of 90.9% of Biofilm producing Staphylococcus species were resistant towards penicillin and erythromycin Conclusion: The study shows Methicillin resistant Staphylococcus species were resistant to most antibiotics and rate of resistance was slightly higher in biofilm producing isolates comparing to other isolates. resistance. Regular surveillance of methicillin resistance Staphylococcus species and routine screening of biofilm production is important.